Highlights from the Inaugural HIV Reservoirs and Immune Control Conference, October 1st-4th 2023, Malahide Ireland - Una O'Doherty; Javier Martinez Picado; Asier Sáez-Cirión (Case Western Reserve University, 2023)
The inaugural FASEB HIV Reservoirs and Immune Control Conference brought researchers together from across the globe to discuss reservoir dynamics in clinical cohorts. It extended over 4 days in the seaside town of Malahide, Ireland. The scientific sessions covered a broad range of topics, including: 1) HIV pathogenesis and control, 2) reservoirs and viral expression, 3) pediatric reservoirs, 4) innate immunity and B cell responses, 5) environmental factors affecting pathogenesis, 6) loss of virologic control, and 7) HIV-2. The following article provides a brief summary of the meeting proceedings and includes a supplementary document with the meeting abstracts.